Assessment of interleukin‐1β, interleukin‐6, and tumor necrosis factor‐Α levels in the peri‐implant sulcular fluid among waterpipe (narghile) smokers and never‐smokers with peri‐implantitis. (16th November 2017) - Abduljabbar, Tariq; Akram, Zohaib; Vohra, Fahim; Warnakulasuriya, Saman; Javed, Fawad
Abstract: Background: It is hypothesized that levels of interleukin (IL)‐1β, IL‐6 and tumor necrosis factor (TNF)‐α are significantly higher in the peri‐implant sulcular fluid (PISF) of waterpipe‐smokers (WS) compared with never‐smokers with peri‐implantitis. Purpose: The aim of the present convenience sample case‐control study was to compare the levels of IL‐6, IL‐1β, and TNF‐α in the PISF of WS and never‐smokers with peri‐implantitis. Materials and Methods: Demographic data was collected using a questionnaire. Peri‐implant probing depth (PPD) was measured and crestal bone loss (CBL) was measured on digital bitewing radiographs. PISF samples were collected using paper strips and the collected PISF volume was determined. levels of IL‐6, IL‐1β, and TNF‐α were measured using enzyme linked immunosorbent assay. Study sample‐size was estimated and statistical analysis was performed. P values less than .05 were considered statistically significant. Results: Sixty‐six individuals (33 individuals in group‐1 and 33 in group‐2) were included. In groups 1 and 2, 41 and 44 implants, respectively were placed. The mean total PPD ( P < .001) and peri‐implant CBL ( P < .001) was statistically significantly higher around implants affected by peri‐implantitis in group‐1 compared with group‐2. The PISF volume ( P < .05) collected and levels of IL‐1β ( P < .01), IL‐6 ( P < .01), and TNF‐α ( P < .01) were statistically significantly higher among individuals in group‐1 compared with group‐2. Conclusion: WS with peri‐implantitis present increased expression of local proinflammatory cytokines in the PISF than never‐smokers.